The Kurdish National Liberation Movement and its Implications in Peshang Magazine (1982-1991) A Historical Study - Omar , Ahmad Hamadameen (Zanco Journal of Human Sciences, 2021)
Following the resumption of the armed struggle in southern Kurdistan in 1976, all Kurdish political parties paid great attention to the journalistic struggle, and in this context, the Kurdistan Democratic People’s Party after its establishment on July 26/1981, issued the People's Newspaper and the Pésheng journal under the supervision of the Central Information Office , The contents of the topics of the Pésheng journal, especially those written about the history of the Kurdish national liberation movement and its circumstances at the time, are very important topics. Because there has been no study on this to the best of the researcher’s Knowledge, this paper was deemed necessary. The paper consists of an introduction, four sections, and conclusions. The first section deals with an overview of the Pésheng journal, in which the supervisors, the place of its publication, its time, numbers, price and purpose are presented.In the second section, the journal’s view on the Kurdish national liberation movement at this point is explained. The third section is devoted to discussing the topics that were written in the journal regarding the history of the Kurdish national liberation movement. The fourth section tackles the conditions of Kurdistan at that time in light of the topics of the Pésheng journal. The paper ended with the conclusions arrived at throughout the study.